Acute Dehydration Impairs Endurance Without Modulating Neuromuscular Function - Barley, Oliver R.; Chapman, Dale W.; Blazevich, Anthony J.; Abbiss, Chris R. (Frontiers in Physiology, 2018)
Introduction/Purpose: This study examined the influence of acute dehydration on neuromuscular function. Methods: On separate days, combat sports athletes experienced in acute dehydration practices (n=14) completed a 3 h passive heating intervention (40˚C, 63% relative humidity) to induce dehydration (DHY) or a thermoneutral euhydration control (25°C, 50% relative humidity: CON). In the ensuing 3 h ad libitum fluid and food intake was allowed, after which participants performed fatiguing exercise consisting of repeated unilateral knee extensions at 85% of their maximal voluntary isometric contraction (MVIC) torque until task failure. Both before and after the fatiguing protocol participants performed six MVICs during which measures of central and peripheral neuromuscular function were made. Urine and whole blood samples to assess urine specific gravity, urine osmolality, haematocrit and serum osmolality were collected before, immediately and 3 h after intervention. Results: Body mass was reduced by 3.2 ± 1.1% immediately after DHY (P<0.001) but recovered by 3 h. Urine and whole blood markers indicated dehydration immediately after DHY, although blood markers were not different to CON at 3 h. Participants completed 28% fewer knee extensions at 85% MVIC (P<0.001, g=0.775) and reported a greater perception of fatigue (P=0.012) 3 h after DHY than CON despite peak torque results being unaffected. No between-condition differences were observed in central or peripheral indicators of neuromuscular function at any timepoint. Conclusion: Results indicate that acute dehydration of 3.2% body mass followed by 3 h of recovery impairs muscular strength-endurance and increases fatigue perception without changes in markers of central or peripheral function. These findings suggest that altered fatigue perception underpins muscular performance decrements in recovery from acute dehydration.